Antecedents of team innovation in health care teams. (19th September 2018) - Moser, Karin S.; Dawson, Jeremy F.; West, Michael A.
Abstract : We extend previous research on team innovation by looking at team‐level motivations and how a prosocial team environment, indicated by the level of helping behaviour and information‐sharing, may foster innovation. Hypotheses were tested in two independent samples of health care teams (N1  = 72 teams, N2  = 113 teams), using self‐report measures. The examples of team innovation given by the individual team members were then rated for innovativeness by independent health care experts to avoid common method bias for the outcome variable. Subsequently, the data was aggregated and analysed at team level. The study was part of a larger data‐gathering effort on health care teams in the UK. Results supported the hypotheses of main effects of both information‐sharing and helping behaviour on team innovation and interaction effects with team size and occupational diversity. Differences in findings between types of health care teams can be attributed to differences in team tasks and functions. The results suggest ways in which helping and information‐sharing may act as buffers against constraints in team work, such as large team size or high occupational diversity in cross‐functional health care teams, and potentially turn these into resources supporting team innovation rather than acting as barriers.